Estratégias para a síntese de compósitos moleculares derivados de poliuretanas - Libanori, Rafael Augusto Nicolosi (Universidade Federal de São Carlos, 2009)
In this work, we investigated strategies to obtain polyurethanebased molecular composites containing metal oxide nanoparticles chemically attached to polyurethane polymeric chain. In Strategy 1, nanoparticles functionalized with OH organic groups were added in a typical reaction to obtain thermoplastic polyurethane. The obtained materials were transparent, presented brown-color and typical characteristics of thermoplastic polymers. The results revealed that the addition of functionalized nanoparticles plays an important role in the chain growth process, suggesting that nanoparticles OH organic groups are consumed during the polymerization process, forming a primary bond between the material components. However, it was not possible to identify that primary bond by the characterization methods used in this work. On the other hand, in the Strategy 2, efforts were spent on the development of methods to obtain functional organic molecules constituted by linear chains with silane groups in both ends (called here as connecting agents). The connecting agents were used as nanobuilding blocks in a condensation reaction with metal oxide nanoparticles in order to obtain a linear hybrid chain with alternated organic and inorganic blocks. Despite it was not possible obtain linear hybrid chain molecular composite, the results contributed to a better comprehension of the mechanism involved in that method, suggesting that the use small nanoparticles (< 10 nm) and large organic molecules (molar mass between 10.000 e 50.000 g/mol) is necessary to synthesize the linear hybrid chain. Furthermore, bifunctional nanoparticles must be used to avoid the formation of a tridimensional network by cross-linking processes.
Strategies for synthesis of polyurethane-based molecular composites
Keywords: Compósitos poliméricos; Poliuretanas; Nanopartículas; Polímeros híbridos; Compósitos moleculares; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA